India in the Rise of Britain and Europe: A Contribution to the Convergence and Great Divergence Debates. (January 2021) - Bhattacharya, Prabir
This article discusses the role of the British control of India in the rise of Britain and Europe as well as in the convergence in incomes within the Atlantic economy in the late nineteenth century. Britain was at the apex of the world economy throughout most of the nineteenth century. The article argues that the emergence of Britain as the apex economic and political power depended on her control over India. This control of India then enabled Britain to pursue a set of policies that were of critical importance, both for the convergence in incomes within the Atlantic economy and the rise of Europe. The thesis advanced here can be viewed, depending on one's prior position, as being either complementary to or alternative to the views of many of the protagonists of the divergence debate in the literature. JEL: N10, N13, N15, N70, O4